Pengaruh Kompensasi, Lingkungan Kerja Fisik dan Motivasi Kerja terhadap Kepuasan Kerja Karyawan - Pertiwi, Tika Ana; Yudy Wijaya, Putu; Gede, I Komang (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The aim of this research is to determine the effect of compensation, physical work environment and motivation on employee job satisfaction at the Asta Sedana Kapal Cooperative, Mengwi Badung. Data collection methods in this research were interviews, observation and questionnaires. Questionnaires were given to 32 respondents, then analyzed using multiple linear regression analysis, coefficient of determination, t-test and F-test. Based on the analysis results, the conclusion from this research is that compensation has a positive and significant effect on employee job satisfaction at the Asta Sedana Kapal Cooperative, Mengwi Badung. The physical work environment has a positive and significant effect on employee job satisfaction at the Asta Sedana Kapal Cooperative, Mengwi Badung. Motivation has a positive and significant effect on employee job satisfaction at the Asta Sedana Kapal Cooperative, Mengwi Badung. Compensation, physical work environment and motivation simultaneously have a positive and significant effect on employee job satisfaction at the Asta Sedana Kapal Cooperative, Mengwi Badung. Suggestions in this research include leaders at the Asta Sedana Kapal Cooperative, Mengwi Badung, motivating their employees to be enthusiastic about working, increasing their attention to security conditions in the workplace such as security against data leaks and security from theft..